Investigations of slip in capillary flow by laser-Doppler velocimetry and their relations to melt fracture - Münstedt, Helmut (AIP Conference Proceedings, 2015)
Flow profiles within a slit capillary are measured by laser-Doppler velocimetry. They allow the direct determination of the slip velocity at the wall. It is demonstrated that the flow profile of the melt of a high density polyethylene (HDPE) already shows slip components at small shear rates. At high shear rates the slip is dominant and a plug flow is found. Furthermore, it is shown that the surface irregularity called "shark skin" is generated at the slit exit by the stretching of surface layers at pronounced elongational rates. These elongational rates are due to the differences between the flow velocities at the wall of the slit and those of the extruded strand. It is shown how "shark skin" may be avoided when the elongational rate is reduced by introducing slip of the melt in the slit using special additives.
Created from Fastlane, Scopus look-up